PENERAPAN SANKSI ADAT TERHADAP TINDAK LANJUT PIDANA PENCURIAN TERNAK: (Studi Kasus di Kecamatan Simpang Tiga) - Safriadi, Safriadi (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2020)
This research aims to find out the form of customary sanctions against the perpetrators of cattle theft crimes and obstacles in the application of customary sanctions against the criminal follow-up of theft as well as the view of Islamic law towards the mechanism of the lifting of customary sanctions for the perpetrators of theft crimes in Simpang Tiga Sub-district. The method used in this study is a qualitative method in the collection of author data using library research methods and field research methods. The results showed that the form of customary sanctions against the perpetrators of the crime of theft of livestock in is to use customary law, and the provision of sanctions against the perpetrators of the crime of theft of livestock based on village deliberations with indigenous figures after the process of arresting the perpetrator of the theft of livestock is given advice, reprimand, perpetrators make apology statements to the victim, as well as compensate all losses from the theft. The obstacles in the application of customary sanctions against perpetrators of the criminal follow-up of cattle theft are the low understanding of the community towards indigenous law, the lack of understanding of the basic duties and functions, not the people who understand about the customary law, the absence of certain community groups who do not want to accept the ruling of customary law, and the lightness of customary sanctions against the perpetrators of theft crimes. The view of Islamic law towards the mechanism of sentencing of customary sanctions for perpetrators of minor theft crimes with the punishment of advice, reprimand, penalty of fines through deliberation and kinship is not contrary to Islamic law.